An Australian incremental guideline for particulate matter (PM2.5) to assist in development and planning decisions - Adam Capon; Jackie Wright (Sax Institute, 2019)
Objectives: Many large-scale developments in Australia, such as road infrastructure, are subject to community concern due to their ongoing emission of particulate matter that may lead to adverse health impacts. The assessment of these impacts is guided by planning and health policies, but these policies have limitations. The objective of this paper is to provide an approach to setting an incremental guideline that can be used by regulators and health professionals to assess the impact of particulate matter from a development on a population, specifically the impact of particulate matter less than or equal to 2.5 micrometres in diameter (PM2.5). Type of program or service: Environmental health policy. Methods: The calculation of PM2.5 concentrations and life days lost using concentration response functions and life tables. Results: We calculated annual incremental concentrations of PM2.5 for a 1 in 1 000 000 increased risk of mortality, a 1 in 100 000 increased risk of mortality and a 1 in 10 000 increased risk of mortality along with associated life days lost. These values can be used to assess the acceptability of PM2.5 health impacts from a development. Lessons learnt: An incremental annual PM2.5 concentration of up to 0.02µg/m3 could be considered negligible, while concentrations between 0.02 and 1.7 µg/m3 could be considered acceptable/tolerable, with concentrations greater than 1.7 µg/m3 considered unacceptable.